Visi Eskatologis-Kreatif dan Eksemplaris-Terbuka sebagai Model Kehadiran Kristen dalam Konteks Indonesia - Christanto Sema Rappan Paledung (Studia Philosophica et Theologica, 2019)
This paper intends to look for a vision of Christian presence that might be applied in the context of a pluralistic society, such as Indonesia. Therefore, I ventured into the tradition of the 20th century Russian Orthodox Church to look for that possibility. It was Nikolai Berdyaev, a Russian theologian who redefined the direction of church in Russia in his day. He expressed a philosophy of creative freedom in the eschatological perspective of the Orthodox Church. He stressed the importance of human participation in the divine work to resist objectification of the world. I will construct the vision of Christian Berdyaev’s presence, I will look at the thoughts of a theologian of a Calvinist Church in Indonesia, namely, namely Kadarmanto Hardjowasito. He expressed his Christian vision which emphasized exemplarity and openness to other individuals and communities as visions of Christian presence. Both thoughts can build a theological construction for visions of Christian presence in the Indonesian context